(untitled) (MMIT Proceedings, 2024)
This article explores the impact of traditionalism on modern education through the lens of cultural exchange. It examines the features of Eastern and Western teaching methods, highlighting the differences in their fundamental principles and approaches to teaching. The role of tradition in the educational process is discussed in both the East and the West, emphasizing its significance for preserving cultural identity and preserving historical heritage. The article analyzes how modernity challenges education and how traditionalism can help address these challenges. It concludes by summarizing the findings and drawing conclusions about the significance of traditionalism within the context of contemporary educational practices and cross-cultural exchange.